Analysis of Promotion Strategies through the Addition of Play Areas with Cats at Mostcat Cafe Batam - Sweiney, Sweiney; Sipayung, Natal Olotua; Ilham, Wahyudi; Alhamdi, Rezki (Jurnal Indonesia Sosial Sains, 2024)
Mostcat Cafe is the first cafe in Batam that integrates the concept of direct interaction with cats. Adopting the "cat cafe" model popular in Taiwan since 1998, this cafe offers a relaxing experience while enjoying food and drinks, as well as the opportunity to interact with various breeds of cats. This study aims to analyze the marketing strategy implemented by Mostcat Cafe, including the Marketing Mix elements: product, price, promotion, and location. The method used is a qualitative approach with in-depth interviews and field observations. The results showed that the addition of a play area with cats increased customer loyalty and frequency of visits, and the price set was in line with the experience provided. Mostcat Cafe succeeded in creating a solution for cat owners and providing a space for cat lovers to gather, thus strengthening the cafe's position in the thematic culinary industry in Batam. This research is expected to provide valuable insights for similar business owners in developing effective marketing strategies.